Pengaruh Promosi Penjualan, Kualitas Pelayanan, dan Kemudahan Terhadap Loyalitas Pelanggan Dompet Digital ShopeePay - Hana Pratiwi; Luthfi Zamakhsyari; Herni Justiana Astuti; Fatmah Bagis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of promotions, service quality and convenience on ShopeePay digital wallet customer loyalty. The method used is a quantitative approach with primary data from 158 students who are active ShopeePay users at three universities in Purwokerto: Jenderal Soedirman University, UIN Prof. K.H. Saifuddin Zuhri, and Muhammadiyah University Purwokerto. The sampling technique used purposive sampling, by distributing questionnaires via Google Form. Data were analyzed using IBM SPSS Statistics 26 through validity, reliability, classical assumptions, F test and t test. The research results show that promotion and convenience have a positive and significant effect on customer loyalty, while service quality has a positive and insignificant effect on customer loyalty. These findings indicate that attractive promotions and ease of use of services play a greater role in forming customer loyalty than service quality alone.